KOMPETENSI KONSELING MULTIBUDAYA GURU BK MADRASAH ALIYAH JAWA TIMUR ALUMNI DIKLAT BDK SURABAYA - Akhmadi, Agus (Balai Diklat Keagamaan Surabaya, 2017)
Diversity (multicultural) is the reality of life. In Madrasah Aliyah, themul ti cul tural phenomenon of students also occurs, due toethnographic, demographi c and status variabl es. In Isl am,diversity is for li-taarofu, knowing and understanding and helping.Counseling assistance to students requires the competence ofmulticultural counseling (KKM). This study describes KKM Guru BKMadrasah Aliyah, including awareness, knowledge and skills ofmulticultural counseli ng and training program of teacher'scompetence improvement BK. This research is a case study withqualitative descriptive. The subject of the research is the teacher ofBK MA alumni of Counseling and Counseling Training at the ReligiousTraining Center of Surabaya. Data collection using questionnairesand interviews. Data analysis was done descriptively qualitative. Theresults showed that, 14 % of teachers BK MA have low competenceand 86% high. Mul ticultural counsel ing as a service to themulticultural client is also increasingly important, so that the trainingfor the increased competence of the BK Teachers is required.Programs of training appropriate to the multicultural component ofcounseling and experimental learning model based on andragogycan be applied to BK Teachers. Increasing the competence ofmulticultural counseling needs to get the attention of Education Hallby designing curriculum and multicultural-oriented syllabus syllabus.